Anti-money laundering legislation in Malaysia: the challenges within - Zul Kepli, Mohd Yazid; Mohd. Yasin, Norhashimah (2015)
This article discusses the legal and regulatory framework currently in place to safeguard the interest of the public, particularly innocent depositors in cases involving Innocent Deposit Taking. The reasons for the rampant and widespread cases of IDT in Malaysia are analyzed, followed by a study on the adequacy of the current legal and regulatory framework. Best practices from other countries are also highlighted. The uniqueness of IDT and the legal dilemma to classify it as money laundering is also covered. The study ends with a series of suggestions and recommendations on how to ensure comprehensive protection for innocent depositors.